1997
DOI: 10.1007/s002130050429
|View full text |Cite
|
Sign up to set email alerts
|

The effects of food deprivation and incentive motivation on blood glucose levels and cognitive function

Abstract: The current study investigated the relationships between blood glucose levels, mild food deprivation, sympathetic arousal, and cognitive processing efficiency. Subjects (n = 82) were randomly assigned to four experimental conditions, comprising combined manipulations of food deprivation and incentive motivation. Baseline and mid-session measurements of blood glucose, blood pressure and pulse rate were taken. Subjects completed a number of measures of cognitive processing efficiency and self report measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 22 publications
3
48
0
Order By: Relevance
“…This is consistent with our findings of a lack of any significant performance decline in the non-speed dependent, predominantly occipital cortex centred one-card learning and one-back memory tasks, which supports the previously demonstrated robustness of these domains [15–17,22] .…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with our findings of a lack of any significant performance decline in the non-speed dependent, predominantly occipital cortex centred one-card learning and one-back memory tasks, which supports the previously demonstrated robustness of these domains [15–17,22] .…”
Section: Discussionsupporting
confidence: 93%
“…However, other studies have shown that missing one or two meals, or fasting for 24 hours causes no consistent detriment in complex cognitive performance. Furthermore, Green et al (1997b) found no relationship between lowered glucose levels as a consequence of missing a meal and cognitive performance. They concluded that the results do not support the proposition that dieting affects cognition via an impact on glucose levels.…”
Section: Introductionmentioning
confidence: 94%
“…Adrenergic antagonists oppose the effects of arousal, but not glucose, on memory (Nielson & Jensen, 1994;Gold, 1995). Furthermore, it has been found that, whereas manipulating arousal levels by means of incentive motivation does produce selective improvements in performance, those improvements are unrelated to blood glucose levels (Green et al 1997a). Indeed, sympathoadrenal arousal during a psychologically challenging performance test does not necessarily lead to any change in plasma glucose in the absence of intake (Hagström-Toft et al 1993).…”
Section: Mechanistic Implicationsmentioning
confidence: 99%
“…A recent meal may interact with the impact of arousal on blood glucose as well as with the effect of further glucose intake (Martin & Benton, 1999). Moreover, fasting has been associated with enhanced speed of performance on memory tasks in some studies (Benton & Owens, 1993;Green et al 1997a), but poorer recall levels in others (Martin & Benton, 1999).…”
Section: Mechanistic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation